The private sector in agricultural R&D: policies and institutions to foster its growth in developing countries - Naseem, Anwar; Omamo, Steven Were; Spielman, David J. (International Food Policy Research Institute, 2006)
New technologies are critical to enhancing agricultural productivity and reducing poverty in many developing countries. While public-sector investment in research has historically driven technological change in agriculture, recent trends suggest that the public sector’s role may not be as significant in the future. There is much optimism about the private sector’s capacity to deliver new technologies, even though current levels of private investment in research in developing countries remain low. This paper examines the determinants of private investment in agricultural research and development in developing countries, the market and institutional constraints that limit private investment growth, and the incentive mechanisms that can strengthen private investment responses in agricultural R&D—from both the demand and supply sides—particularly in relation to pro-poor growth.